Research on dynamic stiffness of the damping element in bellows-type fluid viscous damper by a simplified model. Issue 1 (6th July 2020) - Jiao, Xiaolei; Zhang, Jinxiu; Zhao, Hongchao; Yan, Yong
Abstract : Purpose: Bellows-type fluid viscous damper can be used to isolate micro vibration in high-precision satellites. The conventional model cannot describe hydraulic stiffness in the medium- and high-frequency domain of this damper. A simplified analytical model needs to be established to analyze hydraulic stiffness of the damping element in this damper. Design/methodology/approach: In this paper, a bellows-type fluid viscous damper is researched, and a simplified model of the damping element in this damper is proposed. Based on this model, the hydraulic stiffness and damping of this damper in the medium- and high-frequency domains are studied, and a comparison is made between the analytical model and a finite element model to verify the analytical model. Findings: The results show that when silicone oil has low viscosity, a model that considers the influence of the initial segment of the damping orifice is more reasonable. In the low-frequency domain, hydraulic stiffness increases quickly with frequency and remains stable when the frequency increases to a certain value; the stable stiffness can reach 106 N/m, which is much higher than the main stiffness. Excessive dynamic stiffness in the high-frequency domain will cause poor vibration isolation performance. Adding compensation bellows to the end of the original isolator may be an effective solution. Practical implications: A model of the isolator containing the compensation bellows can be derived based on this analytical model. This research can also be used for dynamic modeling and vibration isolation performance analysis of a vibration isolation platform based on this bellows-type fluid viscous damper. Originality/value: This paper proposed a simplified model of damping element in bellows-type fluid viscous damper, which can be used to analyze hydraulic stiffness in this damper and it was found that this damper showed stable hydraulic stiffness in the medium- and high-frequency domains.